Konflik Sosial dalam Novel Konspirasi Alam Semesta Karya Fiersa Besari Kajian Strukturalisme - Sabila, Gita; Fathurohman, Irfai; Ristiyani (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2022)
This research is motivated by the conflicts contained in a literary work, especially novels. There are various types of conflicts contained in a novel, these conflicts include, external conflicts and also internal conflicts. External conflict is divided into two, namely social conflict and physical conflict, while internal conflict can be called inner conflict. This study focuses on social conflict which is a conflict that occurs and is caused by human contact. The formulation of the problem in this research how the social conflict contained in the novel Konspirasi Alam Semesta by Fiersa Besari? This study aims to determine the social conflicts contained in the novel Konspirasi Alam Semesta by Fiersa Besari. The approach used in this study is a structural approach. This type of research is descriptive qualitative with the aim of describing the social conflicts contained in the novel. This research was conducted by collecting data that had been obtained from reading and recording data activities. The data collected by documentation. Data analysis in this study was carried out by reducing data, assessing data, and drawing conclusions. The results of the research in the novel using structuralism studies show that the social conflicts that occur in the novel Konspirasi Alam Semesta are Juang's childhood conflicts that occurred when Juang was a child, conflicts of opinion and feuds between Juang and his father, and conflicts when Juang was young. Juang was taken prisoner. The social conflicts contained in this study are derived from the social relations between the characters in the novel.